Modification of Polymer Properties by Irradiation Properties of Thermoplastic Electromer after Radiation Cross-linking - Manas, M.; Manas, D.; Stanek, M.; Mizera, A.; Ovsik, M. (Asian Journal of Chemistry, 2013)
Radiation processing involves the use of natural or manmade sources of high energy radiation on an industrial scale. The principle of radiation processing is the ability of high energy radiation to produce reactive cations, anions and free radicals in materials. The industrial applications of the radiation processing of plastics and composites include polymerization, cross-linking, degradation and grafting. Radiation processing involves mainly the use of either electron beams from electron accelerators or g-radiation from cobalt-60 sources. The TPE-E thermoplastic elastomer tested exhibited significant changes in temperature stability and mechanical properties after irradiation. From this point of view, there may be new applications in areas with service temperatures higher than their former melting point. This study compared the temperature stability and mechanical properties of irradiated and non-irradiated TPE-E.